Improving silty sand performance with cement and fiber reinforcement: a study of mechanical behavior - Halimi, Asma; Bourokba, Amal Souad; Ghembaza, Moulay Smaine; Hachichi, Abderlkader (Vojnotehnički glasnik / Military Technical Courier, 2026)
Introduction/purpose: This study aims to valorize a local material from the western region of Algeria for potential use in road construction. The main objective is to investigate the effect of incorporating synthetic polypropylene fibers and natural Alfa plant fibers at varying contents (0%, 0.3%, 0.6%, and 0.9%), on the strength of a silty sand stabilized with 4% cement. Methods: An experimental program was conducted using unconfined compression tests and unconsolidated-undrained triaxial tests. These tests were performed on soil–fiber–cement mixtures compacted statically at the Standard Optimum Proctor (SOP) conditions (dmax= 17 kN/m3 and wopt =16.6%) and cured for 1, 7, and 28 days in open air. Results: The results revealed a significant improvement in the mechanical strength of the treated soil, with a change in the failure behavior from brittle to ductile. The addition of 0.3% fibers enhanced cohesion while reducing the internal friction angle. Furthermore, fiber-reinforced cemented samples exhibited greater stiffness compared to untreated soil. Moreover, the highest unconfined compressive strength was obtained with the combination of 0.9% fiber reinforcement and 4% cement. Conclusion: The reinforcement of cemented silty sand with polypropylene and Alfa fibers significantly improves its mechanical strength and stiffness. The addition of 0.9% fiber content yields the highest compressive strength while effectively transitioning the soil’s behavior from brittle to ductile. These findings confirm that valorizing local Algerian materials is a technically viable and sustainable solution for road infrastructure development.